Electroconvulsive therapy treatment in patients with somatic symptom and related disorders - Leong KW; Tham JCW; Scamvougeras A; Vila-Rodriguez F (Neuropsychiatric Disease and Treatment, 2015)
KaWai Leong,1 Joseph CW Tham,2 Anton Scamvougeras,2 Fidel Vila-Rodriguez3 1Department of Psychiatry, 2BC Neuropsychiatry Program, Department of Psychiatry, 3Non-Invasive Neurostimulation Therapies Laboratory at UBC, Department of Psychiatry, University of British Columbia, Vancouver, BC, Canada Objective: Medically unexplained somatic complaints are highly prevalent, and lead to significant impairment and disability. The number of effective treatment modalities for somatic symptom and related disorders (SSDs) or somatoform disorders (SDs) remains limited. To date, there is no formal indication for electroconvulsive therapy (ECT) in SSD or SD. We report on the largest case series to date regarding the effectiveness of ECT in patients with SSD and SD.Methods: A retrospective chart review of all patients treated with an index course of ECT at the Neuropsychiatric Program at the University of British Columbia Hospital from 2000 to 2010 was conducted. The primary outcomes consisted of changes in pseudoneurologic symptoms, pain symptoms, cardiopulmonary symptoms, and gastrointestinal symptoms. Complaints were examined pre- and post-ECT.Results: Twenty-eight participants were included in this study. Twenty-one participants received right unilateral ECT. Six received bifrontal ECT. One received bitemporal ECT. Eighteen of 21 participants reported improvement in pseudoneurologic symptoms; eleven of 14 participants reported improvement in pain symptoms; one participant reported improvement in cardiopulmonary symptoms; and one of two participants reported improvement in gastrointestinal symptoms. This paper discusses the putative mechanism of action of ECT in the treatment of SD/SSD.Conclusion: This retrospective study suggests that ECT could be included as part of the existing treatment for refractory SSD and SD, particularly in refractory cases with comorbid mood disorders. Keywords: electroconvulsive therapy, somatic symptoms, somatoform disorders